Pengadopsian United Nation Resolution 1325 on Women, Peace and Security: Strategi Pencegahan, Penanganan, dan Pemberdayaan Perempuan dan Anak dalam Konflik Sosial di Jawa Tengah - Sugiarto, Laga; Hidayat, Arif (Jurnal Ilmiah Wahana Pendidikan, 2024)
The need for regulation and implementation related to the protection and empowerment of women and children in conflict situations in Indonesia is crucial considering that women and children are a vulnerable group in conflict situations. The lack of women's participation in the peace and security process as well as the erroneous perception of the need to protect women and children in conflict situations underlies the Government of Indonesia to adopt the UN Security Council Resolution Number 1325 through Presidential Regulation Number 18 of 2014 concerning the Protection and Empowerment of Women and Children in Social Conflict (P3AKS). The Implementation of Presidential Regulation No. 18 of 2014 concerning P3AKS needs to be carried out as an implementation of the Mandate of the Regulation of the Coordinating Minister for People's Welfare of the Republic of Indonesia Number 7 of 2014 concerning the National Action Plan for the Protection and Empowerment of Women and Children in Social Conflict (RAN P3AKS) 2014-2019. Protecting them makes an effort to prevent and overcome all forms of violence and violations of the human rights of women and children as well as fulfilling the components of basic needs services in conflict management as an integral part of conflict management activities. Meanwhile, the meaning of empowering women and children is interpreted as an effort to strengthen human rights, improve the quality of life and increase the space for women and children's participation in peacebuilding. The protection and empowerment of women and children in conflict aims to protect, respect, and guarantee women's human rights in conflict resolution.